COVID-19: knowledge and attitudes of hospital staff of a large Italian teaching hospital. (30th September 2020) - Moro, M; Vigezzi, G P; Capraro, M; Biancardi, A; Nizzero, P; Signorelli, C; Odone, A
Abstract: Background: During infectious disease emergencies, fully aware healthcare workers (HCWs) and public services staff are unique resources to keep health systems active and tackle epidemics. Aim of the study was to assess concern, general and health-related knowledge (case management and Infection Prevention and Control [IPC] measures) among hospital staff on SARS-CoV-2 in Lombardy region (Italy). Methods: One week after WHO declared COVID-19 a public health emergency we developed and online administered a 7-item questionnaire to all staff of San Raffaele Hospital, a referral and teaching hospital in Milan, exploring knowledge and attitudes on COVID-19. The survey remained accessible online for 72 hours. Results: A total of 2, 046, including HCWs and other staff, answered the survey (response rate 25%). Among the 2, 027 responders included in the analysis, 1, 102 were HCWs (54%), also in training, and 924 non-HCWs (46%). 60% of responders reported being worried or extremely worried about the epidemic. Concerning knowledge, the survey asked about modes of transmission, clinical forms, preventive measures in everyday life in Italy and cough etiquette. There were uniform trends in the two groups: HCWs were more aware and answered more properly (mean of correct answers 71, 6%) than non-HCWs (mean 61, 2%). HCWs were asked about IPC precautions, with only 41% providing correct answers, while over 74% knew only supportive therapy is currently available against COVID-19. Conclusions: We were among the first to explore hospital staff knowledge on COVID-19 reporting data from a large study population. HCWs were slightly less concerned but more knowledgeable than general staff. Last questions showed that among HCWs there is generally good knowledge on the topic. However, most of the responders missed the recommendations to adopt simultaneously standard, contact and airborne precautions plus eye protection managing suspected and confirmed cases, as proposed by national and international authorities. Key messages: During the ongoing emergency, it is of utmost importance that hospital staff is adequately trained to implement the best IPC measures and limit the spread of the infection. Our data can inform planning of these preventive measures.